Broadband polarization conversion based on small-size metamaterial in the GHz band - Ha, Duong Thi; Ve, Tran Quoc; Dung, Dinh Ngoc; Tung, Bui Son; Hien, Nguyen Thi; Hanh, Vu Thi Hong; Khuyen, Bui Xuan; Lam, Vu Dinh (Vietnam Journal of Science and Technology, 2021)
We proposed a small GHz metamaterial perfect absorber, which can operate in two different functional modes depending on the orientation of unit-cell structure. Firstly, when the unit-cell structure is oriented symmetrically to the external electric-field direction, an absorption mode is achieved with a near perfect absorption peak. Secondly, by rotating the resonator structure on top layer, metamaterial is asymmetric to the external field, leading to the excitation of cross-coupling effect.